2013
DOI: 10.1051/epjconf/20134006011
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic flux concentration methods for magnetic energy harvesting module

Abstract: Abstract. This paper presents magnetic flux concentration methods for magnetic energy harvesting module. The purpose of this study is to harvest 1 mW energy with a Brooks coil 2 cm in diameter from environmental magnetic field at 60 Hz. Because the harvesting power is proportional to the square of the magnetic flux density, we consider the use of a magnetic flux concentration coil and a magnetic core. The magnetic flux concentration coil consists of an aircore Brooks coil and a resonant capacitor. When a unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The electrical power collected from leakage magnetic flux is proportional to the quality factor of the leakage flux recovery coil [4]. However, the AC resistance increases due to the skin effect and a proximity effect when the magnetic flux crosses a coil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical power collected from leakage magnetic flux is proportional to the quality factor of the leakage flux recovery coil [4]. However, the AC resistance increases due to the skin effect and a proximity effect when the magnetic flux crosses a coil.…”
Section: Introductionmentioning
confidence: 99%
“…V is the induced voltage when the magnetic flux that crosses the coil. L and R is the inductance and resistance of the coil, respectively R L is the output resistance and that is connected to the coil and to capacitor C. From Faraday's law, the induced voltage V of the leakage flux recovery coil is given by (1) [4].…”
Section: Introductionmentioning
confidence: 99%
“…It may enough energy to activate a wireless sensor node, and "oneshot" signal. It was also mentioned the benefit of magnetic flux concentration core [11]. The theoretical design have revealed that the harvesting power is proportional to the fifth power of the outer diameter [12].…”
Section: Introductionmentioning
confidence: 99%
“…Because the target is a weak magnetic field defined by ICNIRP2010 guideline, magnetic flux concentration methods are key techniques. In previous report, the importance of magnetic flux concentration core and coil was experimentally demonstrated [3]. The harvesting power is proportional to the square of the magnetic flux density, therefore it is very important to design the effective permeability of the core defined by the concentration ratio of magnetic flux density to the coil.…”
mentioning
confidence: 99%